Optimizing The Utilization Of Bamboo as a High-Value Craft Based on Community Empowerment (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Bokak Village, Sebumbun, Regency Sekadau, West Kalimantan has abundant potential for bamboo, but its utilization is still limited to traditional use with a low economic mark. Research. This aim is to optimize the utilization of bamboo as a craft worth economy tall through community empowerment. The method used is a descriptive qualitative method with a sample size consisting of 20 people from the Mother House stairs and groups. Data collection techniques were carried out through observation, interviews, and documentation, which were analyzed through stages of data reduction, data presentation, and data extraction. Research results show that around 80% of participants experience improvement in skills in manufacturing craft bamboo, and 60% of participants are capable of producing independently. The products produced in the form of baskets and containers, woven experience improvement quality from the aspect of neatness and value aesthetics, as well as their own potential for marketing. Activities this also opens opportunity business based House stairs, although still there are constraints on aspects of variation design, finishing techniques, and access to marketing. Overall, the optimization utilization of bamboo through public empowerment has proven effective in increasing skills and potential economic society, as well as contributing to the development of a creative economy based on local.